The Construction of a Standard Karyotype of Intermediate Wheatgrass and Its Potential Progenitor Species - Lin Wang; Shuang Liang; Fei Qi; Yinguang Bao; Richard R.-C. Wang; Xingfeng Li (Plants)
The genome composition of intermediate wheatgrass (IWG; Thinopyrum intermedium (Host) Barkworth and D.R. Dewey; 2n = 6x = 42) is complex and remains to be a subject of ongoing investigation. This study employed fluorescence in situ hybridization (FISH) to analyze the karyotype of Th. intermedium and its related species. With the St2-80 probe derived from Pseudoroegneria strigosa and the pDb12H probe from Dasypyrum breviaristatum, FISH analysis classified the chromosomes of Th. intermedium as JvsJvsJrJrStSt. FISH karyotype was established using pSc119.2-1, (GAA)10, AFA-3, AFA-4, pAs1-1, pAs1-3, pAs1-4, and pAs1-6 as a combined multiplex oligonucleotide probe. MATO software was used to analyze chromosome length, arm ratio, and karyotype structure. The karyotype formula of Th. intermedium is K(2n) = 6X = 42 = 36m + 6sm, and that of Th. junceiforme is K(2n) = 4X = 28 = 22m + 6sm. The karyotype formula of Th. elongatum and Th. bessarabicum is K(2n) = 2X = 14 = 12m + 2sm, of Ps. spicata is K(2n) = 2X = 14 = 2M + 12m, and of Da. villosum is K(2n) = 2X = 14 = 12m + 2sm. Based on the results of FISH, standard karyotypes of Th. intermedium and its potential progenitor species were constructed. These standard karyotypes revealed that there was evolutionary parallelism between genome and karyotype, but due to the complexity of evolution, the FISH signal of Th. intermedium was abundant and asymmetrical.